2016
DOI: 10.1177/0886368717737160
|View full text |Cite
|
Sign up to set email alerts
|

Salesforce Control Systems: A Review of Its Consequences Across Continents

Abstract: Over the past 30 years, researchers from all over the world have studied the phenomenon of salesforce control systems. They have analyzed the impact of salesforce control system on different salesperson and organizational variables. As the selling environment is changing, it is important to know what importance salesforce control system holds in different parts of the world. Taking this into account, this study attempts to review the literature on salesforce control systems across continents such as America, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Future researchers will get an idea as to how salesforce control systems work in the pharmaceutical industry in India. As part of a review, Fatima (2016) concluded that research on salesforce control systems has been extensively done in the United States and the United Kingdom, and this study adds to the existing knowledge of salesforce control systems.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Future researchers will get an idea as to how salesforce control systems work in the pharmaceutical industry in India. As part of a review, Fatima (2016) concluded that research on salesforce control systems has been extensively done in the United States and the United Kingdom, and this study adds to the existing knowledge of salesforce control systems.…”
Section: Discussionmentioning
confidence: 98%
“…Salesforce control systems have consequences for salesforce performance (Oh et al, 2021), salesforce motivation, sales organization effectiveness (Fatima, 2016;Fatima & Azam, 2017a, 2017b, servicesales ambidexterity (Ahmad et al, 2022), and salesforce adaptive selling behaviour (Shin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Salesforce control systems have been found to have an impact on cognitive and affective dimensions of intrinsic and extrinsic motivation. Salesforce motivation is important for organizations as it has a direct impact on salesforce behaviors and sales performance, which ultimately leads to sales organization effectiveness (Fatima, 2016).…”
Section: Discussionmentioning
confidence: 99%